Trophic transfer of lipids and fatty acids across habitats in tropical river food webs. (26th February 2022) - O'Mara, Kaitlyn; Venarsky, Michael; Stewart‐Koster, Ben; McGregor, Glenn; Schulz, Cameron; Marshall, Jonathan; Bunn, Stuart E.; Kainz, Martin J.
Abstract: Polyunsaturated fatty acids (PUFA) are essential components of cell membranes and reproductive and sensory organs in vertebrates and are largely acquired through their diets. Accordingly, identification of the dietary sources of PUFA is an important consideration in food web studies. We collected fish, macroinvertebrates (aquatic and terrestrial), and plants (aquatic and terrestrial) from floodplain and river channel habitats in a tropical river catchment in northern Australia, to identify food sources and habitats that provided lipid and PUFA rich food that sustain fish populations. The composition of most FA in fish was similar to that reported from other freshwater tropical environments, with the exception of their higher arachidonic acid content. Fish were found to derive their fatty acids primarily from aquatic sources of food and had similar FA composition to aquatic macroinvertebrates. Aquatic macroinvertebrates fed on aquatic plants (algae) and had higher total lipids and FA contents than plants and fish, providing a more concentrated source of PUFA for fish. Fish obtained most of their FA from their diet except for docosahexaenoic acid (DHA), which they must synthesize due to low DHA in algae and macroinvertebrates. There was no overall difference in basal dietary FA composition between floodplain and river channel habitats. However, macroinvertebrate taxa varied in their lipid and PUFA content. Food quality for fish may therefore vary between habitats as a consequence of differences in macroinvertebrate community composition. Given the high algal production on floodplains compared to the river channels, these habitats are likely to represent the major source of high quality food for fish and other aquatic consumers, and conserving habitats that are rich in lipids and PUFA is important for maintaining healthy fish communities.